KEPUASAN MAHASISWA DALAM PENERAPAN WEBSITE DENGAN MEDIA E-LEARNING/E-EDUCATION MOODLE MATERI MIK I - M. Syairaji; Dian Budi Santoso (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
AbstractGreat opportunities of the national education system to institusion for education using electronic learning aidsand e-learning (web based) that rely on information technology and communication excellence. The informationobtained on the basis of medical records in the course competencies in the Health Information Management PartI (HIM I) is still very limited. Learning system is monotonous. Another thing, the perceived difference in thequality of material received admission affecting the quality of human resources empowerment of the learners.This study aims to get the satisfAaction level of students in the application of web as a medium e-learning/eeducationon material in the Health Information Management Part 1 Administrator Healt InformationManagement students Polytechnic Ministry of Health Public Tasikmalaya. Type of research is a qualitativeaction research. Methods indept interview on the subject of the studi, namely the management, all materiallectures studens and Health Information Management Part I. The research sample was 40 students first half,with the support of 8 people and 1 chairman, lecturer, chairman of the Information Tecnology and Informationtechnology personnel. Data were analyzed descriptively and qualitatively. Measurements performed on endusersatisfaction (end-user) which includes faculty and students. Evaluation questionnaires, and interviewswith the benchmark yield above average median 3. The use of e-learning with Moodle 3.40 shows the meanresults, with a range of value between 3.25 to 3.5. User satisfaction (user) students assessed in terms of benefits,needs, barriers or obstacles and factors that drive. Users who are not satisfied based on a feature of facilityvery less and there is a feature to link tasking related fot students in the Health Information Management. Thematerial is incomplete and lack in Human Resources Information Technology in the manufacturing process,affect the slow development of Moodle used, where success is determined management support system thatis still not. Of adequate technology aspect of hardware and software support with 24 hour internet access.Keywords: student satisfaction, website, e-learning, Moodle, Health Information Management Part 1.AbstrakPeluang besar Sistem Pendidikan Nasional (SISDIKNAS) kepada institusi pendidikan untuk menyelenggarakanpendidikan dengan menggunakan alat bantu pembelajaran elektronik atau e-learning (web based learning) yangmengandalkan keunggulan tehnologi informasi dan komunikasi. Sampai saat ini informasi yang didapatkantentang rekam medis dalam dasar kompetensi mata kuliah Manajemen Informasi Kesehatan (MIK) I masihsangat terbatas. Sistem pembelajaran masih monoton, perbedaan persepsi penerimaan kualitas materi yangditerima, berpengaruh pada pemberdayaan kualitas Sumber Daya Manusia (SDM) yang diajar. Penelitianini bertujuan mendapatkan informasi tingkat kepuasan mahasiswa dalam penerapan website e-learning/eeducationmoodle materi MIK I di Jurusan PIKES Poltekkes Kemenkes Tasikmalaya. Jenis penelitian actionresearch bersifat kualitatif. Metode indept interview pada subyek penelitian (pihak manajemen, seluruhmahasiswa dan dosen MIK I). Sampel 40 mahasiswa PIKES Semester I, dengan pendukung 8 orang dariKetua Jurusan, dosen mata kuliah, kepala Unit IT dan tenaga IT. Data dianalisis secara diskriptif dan kualitatif.Pengukuran kepuasan dilakukan terhadap pengguna akhir (end-user) yang meliputi dosen dan mahasiswa.Evaluasi kuesioner dan wawancara dengan patokan hasil rata-rata diatas angka median 3. Penggunaan aplikasimenunjukkan rerata hasil 3.40 dengan rentang nilai 3,25-3,50. Kepuasan pengguna (user) mahasiswa dinilaidari segi kemanfaatan, pemenuhan kebutuhan, hambatan atau kendalanya dan faktor-faktor yang mendorong.Pengguna yang menyatakan tidak puas didasarkan pada fitur atau fasilitas yang terbatas. Belum adanya fitur untuk link penarikan tugas, materi yang kurang lengkap dan kurangnya SDM IT dalam proses pembuatan,mempengaruhi lambatnya perkembangan Moodle yang digunakan. Keberhasilan omput sangat ditentukandukungan manajemen yang dirasa kurang, Aspek teknologi cukup memadai dari dukungan hardware dansoftware dalam akses internet 24 jam.Kata Kunci: Kepuasan mahasiswa, website, e-learning, Moodle, MIK I